Nghiên cứu định lượng hóa ảnh hưởng của tuyến đường Hồ Chí Minh đến phát triển kinh tế xã hội các huyện có tuyến đường đi qua - Ý, Trần Văn; Thịnh, Nguyễn Viết; Chinh, Nguyễn Thế; Trí, Ngô Đăng; Hậu, Nguyễn Xuân; Chi, Trần Thùy (Vietnam Journal of Earth Sciences, 2012)
SUMMARYTo quantify the impacts from Ho Chi Minh highway to socio-economic development of the districts along it Development of transport network impactsdeeply to socio-economic development of area where it located. The Ho Chi Minh highway is the second one which goes through the Vietnam territory. When this highway has been accomplished, it causesmany multi-form and multi-dimensional impacts in various scales. In this study, the authors applied accessibility methods to quantify the impacts from Ho Chi Minh highway to socio-economic developmentof districts which the route crosses. This method used spatial information layers (terrain, rivers, roads, facilities points, etc.) to simulate the impacts of Ho Chi Minh highway by appraising travel cost of people to the highway and accessibility level of people tolocal social facilities of each district. The result shows that in the same district, there are some regions where people access easily and some regions people has limited access. Especially, the result also points outareas of high accessibility are predominant.